Distinct Signaling Pathways Distinguish in vivo From in vitro Growth in Murine Ovarian Follicle Activation and Maturation - Amoushahi, Mahboobeh; Lykke-Hartmann, Karin (Frontiers in Cell and Developmental Biology, 2021)
Women with cancer and low ovarian reserves face serious challenges in infertility treatment. Ovarian tissue cryopreservation is currently used for such patients to preserve fertility. One major challenge is the activation of dormant ovarian follicles, which is hampered by our limited biological understanding of molecular determinants that activate dormant follicles and help maintain healthy follicles during growth. Here, we investigated transcriptomes of oocytes isolated from dormant (primordial) and activated (primary) follicles under in-vivo and in-vitro conditions. We compared the biological relevance of the initial molecular markers of mature metaphase II (MII) oocytes developed in vivo or in vitro. The expression levels of genes involved in the cell cycle, signal transduction and Wnt signaling were highly enriched in oocytes from primary follicles and MII oocytes. Interestingly, we detected strong downregulation of the expression of genes involved in mitochondrial and reactive oxygen species (ROS) production in oocytes from primordial follicles, in contrast to oocytes from primary follicles and MII oocytes. Our results showed a dynamic pattern in mitochondrial and ROS production related genes, emphasizing their important role(s) in primordial follicle activation and oocyte maturation. The transcriptome of MII oocytes showed a major divergence from that of oocytes of primordial and primary follicles.